Surface Level Solar Ultraviolet-B Radiation At Penang - Karuppusamy, Arunasala Pandy Ail (2006)
Broadband photometric measurements of solar UV-B, UV -A, global and diffuse radiation were made at Universiti Sains Malaysia (USM), Penang from 1994 to 2001. Results from this study show that the large temporal variations for the measured solar radiation is due to the dominant effect of solar zenith angle and clouds. Under all sky conditions, the mean daily total radiation values for the UV-B, UV-A and global radiation were 1.514 x 104 J m-2, 4.69 x lOS J m-2 and 1.80 x 107 J m-2 respectively. For cloudless sky days, the daily maximum UV-B and global irradiance were 1.372 W m-2 and 1.423 kW m-2. The measured effective UV-B irradiance was converted to the erythemal UV flux to relate it to the potential harmful effects due to UV exposure; UVB flux level is in the High or Extreme ranges between 1030 and 1530 hours local time. A study of the diurnal variation of the solar UV -B, UV-A and global radiation show that for similar zenith angles, the solar irradiance after solar noon is larger than that before solar noon. This assymmetrical effect is attributed to the scattering of solar radiation by clouds. Seasonal variation studies show a constant periodicity for the solar UV-B, UV-A and global flux with maximums in March and September. Using available meteorological parameters and total column ozone data, their effects on the surface level solar UV -B radiation was investigated. A mathematical model to estimate the surface level solar UV-8 radiation was also developed and compared with two established model. The spectral model performance is good with a mean error of9.9%. To compliment the spectral model, a simple empirical model was also formulated using multivariate analysis. The mean error of the empirical model was 2.5%.